Systematic Literature Review: Continuity of Midwifery Care Implementation in Various Contries - Fitria Jannatul Laili; Zakiah Zakiah (JURNAL KEBIDANAN BESTARI, 2022)
Indonesia has many problems in maternal and perinatal periods. Maternal and child mortality rates in Indonesia is still high. In Indonesia, Midwives conduct Continuity of Midwifery Care Model as a alternative of taking care of mothers and babies. This Study aims to know continuity of midwifery care (CoMC) implementation in various counties. This study followed the PRISMA guidelines for systematic reviews, a literature search was carried out to assess articles that explain how midwives or midwifery students conduct CoMC. Indonesian Midwives can improve their taking care model for mother and babies by CoMC. Keywords: Continuity of Midwifery Care, CoMC, Midwives, Midwivery Students